Middle Iron Age tombs from Noratus (Sevan region, Armenia) - Yengibaryan, Nora (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
The cemetery under discussion is located to the north of Noratus village (Gegharkunik region, Republic of Armenia), on the left side of the Sevan-Vardenis highway, in the neighbourhood of the fortress-settlement called ‘Seven Springs’. It was excavated during 1989-1990. The subject of this study are three tombs (nos 18, 21 and 22) belonging to the Middle Iron Age (8th-6th centuries BC) and corresponding to the period of expansion of the Urartian Kingdom in the northern territories of the Armenian Highland. The tomb no. 22 was destroyed during agricultural works and the tombs no. 18 and 21 were managed to excavate. The materials unearthed from the mentioned tombs (pottery, weapons, objects related to the horse harness, working tools and embellishments, objects of adornment and outfit as well as seals) demonstrate the high level of material culture in the region, known as Uduri-Etiuni in Urartian written sources. The archaeological materials considered in this study coincide with historical data on coexistence of local and imported elite traditions of material culture within the same region.